2014
DOI: 10.1007/s00705-013-1951-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of group A rotavirus in swine in Canada

Abstract: Group A rotaviruses (RVA) in pigs have been poorly investigated in Canada. In a continued effort to fill this gap, ten finisher swine farms in Quebec, Canada, were sampled over a nine-month period. The presence of RVA was detected in healthy pigs on all farms investigated during the entire sampling period. The genotypes detected included G2, G5, G9 and G11; P[6], P[7], P[13], P[27] and P[34]; and I5 and I14. The predominant types were G2, P[13] and I5, which is different from previous global reports. Various f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 55 publications
2
10
1
1
Order By: Relevance
“…Zoonotic clinical rotavirus (RV) infections as well human–animal re‐assortants have been reported (Bányai et al., ,b). RV RNA has been detected on nine of ten Ontario pig farms (Lamhoujeb et al., ) and nine of ten Québec finisher farms (Lachapelle et al., ); the former study recommended continued surveillance for emerging animal and human RV strains.…”
Section: Introductionmentioning
confidence: 99%
“…Zoonotic clinical rotavirus (RV) infections as well human–animal re‐assortants have been reported (Bányai et al., ,b). RV RNA has been detected on nine of ten Ontario pig farms (Lamhoujeb et al., ) and nine of ten Québec finisher farms (Lachapelle et al., ); the former study recommended continued surveillance for emerging animal and human RV strains.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding RVA, rare VP7 and VP4 genotype strains have been isolated from asymptomatic animals (Abe et al, 2009(Abe et al, , 2011Steyer et al, 2007). Asymptomatic RVA infections are also known to be caused by common genotype strains in pigs (Collins et al, 2010;Lachapelle et al, 2014;Parra et al, 2008). However, some research groups have reported that rare genotype RVAs occasionally cause epizootic diarrhea in adult cattle, a phenotype not usually associated with RVA (Fukai et al, 2007;Masuda et al, 2014;Sato et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…G5 and P[7] are historically considered the most prevalent G and P RVA genotypes in swine, respectively (18). However, recent studies have shown that RVA G9 and G12 genotypes are emerging worldwide in humans and swine (2,(19)(20)(21)(22)(23). …”
mentioning
confidence: 99%